STRATEGI PENGEMBANGAN KOMPETENSI DOSEN DI STIE MANDALA JEMBER - Tamriatin Hidayah (RELASI : JURNAL EKONOMI, 2018)
This research is aimed to formulate how strategy of increasing human resource competence (lecturer) in STIE Mandala Jember . The analysis method used is Multiple Linear Regression and SWOT Analysis. Based on the analysis of Multiple Linear Regression proved significantly that the competence is influenced by the variables of Motivation, Self character, Self concept, Skill and Knowledge, while through SWOT analysis on Hold and Maintain positions, it can be interpreted that the implementation of lecturer competence can be maintained but there is the possibility of development and improvement of its implementation. Some development strategies that can be done are: Development of Pedagogical Competence, Competence Development related to Information Technique, Development of Management Competence / Administration, Curriculum Competency Development, Development of Scientific Competence (Research, Community Service and Publication), Development of Competence Evaluation, and Development of Personal Competence . some programs that can support the development of lecturers competence are: Optimizing the cooperation that has been established with outsiders, can as an alternative source of funds and as a place of conducting research and Community Service, Improving the coordination between existing sections such as Prodi and P3M, foster pride as lecturer as well as rejuvenation of spirit as lecturer. Keywords: competence of lecturer, college, SWOT